The Level of Teachers Implementation of Quality Assessment Practices Standards in Public Schools in the Kingdom of Bahrain - Alawadhi , Ahmed M.; Alomari , Hassan (Dirasat: Educational Sciences, 2024)
Objectives: The current study aimed to investigate l the level of teachers’ implementation of quality assessment practices in the Kingdom of Bahrain. Methods: This study followed a descriptive analytical approach, and the study sample consisted of 430 teachers from various stages of education. The study used a stratified random sampling. To achieve the study objectives, an inventory of assessment practices quality standards was developed, consisting of 53 items distributed across five domains: development of assessment tools and methods, grading and score monitoring, reporting assessment results, ethical assessment practices, and utilization of assessment results. The psychometric properties of the final version of the list were verified. Results: The study results revealed that teachers' implmemtation levels of quality assessment practices standards were high in all survey domains and overall. The means for the domains ranged from (3.08) to (3.44), with the domain of development of assessment tools and methods having the lowest mean, while the domain of ethical assessment practices had the highest mean. The study also indicated statistically significant differences at a significance level of (α=0.05) in the practice level attributed to the variables of qualification, favoring bachelor's degree holders, and undergoing training in measurement and evaluation, as well as those who received more specialized courses in test construction and measurement. However, no statistically significant differences at a significance level of (α=0.05) were found for the variables of gender, teaching stage, and years of experience. Conclusions: The study revealed that teachers' practice levels of quality assessment practices standards were high. The study recommended the need for a similar study in private schools and the continuation of supporting and enhancing training policies and programs at the Ministry of Education to assess student achievement.